Incidence of endometriosis in female sterility. - Olórtegui Acosta, Walter (2015)
The issue of Endometriosis and Infertility looms large in clinical research in recent years. This is reinforced by the numerous publications that approach the problem from its various angles. Endometriosis is a condition that is increasingly being diagnosed more frequently, partly because of an actual increase in incidence, but especially for the growing and increasingly accepted use of laparoscopy as a diagnostic procedure in female infertility.